1988
DOI: 10.1128/jvi.62.4.1186-1193.1988
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the tail sheath gene of bacteriophage T4 and amino acid sequence of its product

Abstract: The nucleotide sequence of gene 18 of bacteriophage T4 was determined by the Maxam-Gilbert method, partially aided by the dideoxy method. To confirm the deduced amino acid sequence of the tail sheath protein (gpl8) that is encoded by gene 18, gpl8 was extensively digested by trypsin or lysyl endopeptidase and subjected to reverse-phase high-performance liquid chromatography. Approximately 40 peptides, which cover 88% of the primary structure, were fractionated, the amino acid compositions were determined, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In phi812, the cryo-EM density in the domain IV region has been described to contain 2 major helices [11]. The region has not been described from the T4 studies because of the limited structural information [8,31,32], but we have also observed these two helices in our phage G gp178 cryo-EM density (Figures 6 and 7).…”
Section: Phage G Tail Sheath Subunit Structure and Arrangementmentioning
confidence: 54%
See 1 more Smart Citation
“…In phi812, the cryo-EM density in the domain IV region has been described to contain 2 major helices [11]. The region has not been described from the T4 studies because of the limited structural information [8,31,32], but we have also observed these two helices in our phage G gp178 cryo-EM density (Figures 6 and 7).…”
Section: Phage G Tail Sheath Subunit Structure and Arrangementmentioning
confidence: 54%
“…It is also the least re portion of the sheath protein density (Figure 7A). The density for domain II is not a as it is described for T4 [33,31], which could be due to phage G's sheath protein, (579 amino acids), being smaller than T4′s gp18 (659 amino acids) [31]. In phage G At the domain level, phage G's sheath protein appears to be similar to the sheath protein of T4, gp18 [6], as labeled in Figure 7B.…”
Section: Phage G Tail Sheath Subunit Structure and Arrangementmentioning
confidence: 88%
“…A complex between gpl8 and gpl9 was also seen, but considering the extensive overlap between the core and sheath, we expected to see a much higher yield of complexes involving these two proteins. It seems unlikely that the lack of cross-linking would be due to inaccessibility to the center of the tail, given the apparently open structure of the sheath as revealed by optical diffraction (14,31,44), or to the lack of reactive groups, since both proteins contain numerous lysine residues (2,3). This may indicate that once the sheath is fully polymerized, there is only limited interaction with the core in readiness for the opposing movements of the sheath and care during contraction.…”
Section: Discussionmentioning
confidence: 99%
“…Bar,100nm. hydrophobic balance of the amino acids of phage head proteins in ethanol sensitive-phages indicates hydrophilicity whereas that in ethanol-tolerant phages indicates hydrophobicity (Yamashita et al, 2000) . Arisaka et al (1988) reported the amino acid composition of the tail sheath protein of the T-4 phage. We calculated the hydrophilic-hydrophobic balance of the tail sheath protein of the T-4 phage of Arisaka by our method.…”
mentioning
confidence: 99%
“…It was reported that the contracted tail sheath could be prepared by heat treatment at 55°C for 5 min (Yamamoto and Uchida, 1973) . It was reported that the tail sheath protein is a GTP-binding protein (Serysheva, et al, 1984) , nucleoside triphosphate and Ca binding protein (Wahl and Kozloff, 1962) and that it is a region homologous to the corresponding region in Ca2+binding proteins, indicating that Ca2+ might be important for stabilizing the native structure of the sheath protein (Arisaka et al, 1988) . From these data, it is suggested that ethanol at 30% (v/v) acts on Ca2+ and GTP or ATP of the sheath proteins, resulting in the shrinkage of such proteins.…”
mentioning
confidence: 99%